Periendoscopic Care Continuum in Acute Cholangitis Caused By Common Bile Duct Stone - Rabbinu Rangga Pribadi; Vesri Yoga; Manu Tandan; Abdul Aziz Rani; Dadang Makmun (Acta Medica Indonesiana)
Acute cholangitis (AC) is a biliary tract infection with in-hospital mortality rates reaching up to 14.7%. The underlying condition is biliary obstruction caused by benign and malignant etiologies, as well as bacteriobilia, with commom bile duct (CBD) stone being one of the most common causes. Currently, the diagnosis is validated using Tokyo Guidelines 2018 criteria. Acute cholangitis due to CBD stone should be managed in a comprehensive manner, i.e., periendoscopic care continuum, consisting of pre-endoscopic care, endoscopic management, and post-endoscopic care. Pre-endoscopic care is primarily comprised of supportive therapy, antibiotic administration, optimal timing of endoscopic retrograde cholangiopancreatography (ERCP), pre-ERCP preparation, and informed consent. Endoscopic management is biliary decompression with stone extraction facilitated via ERCP procedure. Selective biliary cannulation should be performed meticulously. Bile aspiration and minimal bile duct contrast injection should be done to minimize the worsening of biliary infection. Endoscopic biliary sphincterotomy, endoscopic papillary balloon dilatation, and/or endoscopic papillary large balloon dilatation are all safe procedures that can be used in AC. Special precautions must be undertaken in critical and severe acute cholangitis patients who may not tolerate bleeding, in whom endoscopic biliary sphincterotomy may be postponed to decrease the risk of bleeding, and biliary decompression may be only attempted without CBD stone extraction. Nasobiliary tubes and plastic biliary stents are equally effective and safe for patients who have only undergone biliary decompression. In post-endoscopic care, management of adverse events and observation of therapy response are mandatory.